Pengaruh Penggunaan Media Sosial Tiktok Terhadap Karakter Siswa Kelas XI Di SMA Negeri 1 X Koto Singkarak - silviya chaniago; Desi Armi Eka Putri; Ikhwan . (Jurnal Pendidikan, Sains Dan Teknologi, 2026)
This research is motivated by the low character of students at SMA Negeri 1 X Koto Singkarak which is allegedly influenced by the use of TikTok social media. The purpose of the study was to determine the influence of TikTok social media use on the character of grade XI students at SMA Negeri 1 X Koto Singkarak. This type of research is descriptive with a quantitative approach. The research population is 183 students in grade XI for the 2024/2025 school year, with the cluster random sampling technique a sample of 65 people was obtained. The data analysis technique used is simple linear regression. The results of the study showed that the use of TikTok social media had a positive and significant effect on students' character with a contribution of 11.7%. The calculated t value of 2.885 is greater than the t of table 1.669 at a significance level of 0.05, so the hypothesis is accepted. Based on these results, it can be concluded that the use of TikTok social media has an influence on students' characters. The suggestion for students is to be able to manage the time of using TikTok social media so that they are more focused on learning and wiser in utilizing social media.